Conducting Concept Test as a Part of Product Development to Achieve Product/Market Fit for Jola Skirt House - Melati Auzriani G, Zesyara; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2019)
Abstract – Fashion is a business sector that never dies. In Indonesia, out of 2.5 million companies in creative sectors, 1.3 million are in fashion industry, where they contributed to 50% of National GDP. Jola Skirt House decided to do something about the statistic and enter this industry. Jola targets niche market with a unique differentiated product, but is facing problems upon entering the market. The sales number is decreasing, stocks are piling up, only one product dominates the sales count and it seems like current customers are saturated without new product. A question emerged: has Jola products achieved product-market fit? To answer the question, 5 people were interviewed. From this step, it was found that both product-market fit and problem-solution fit were confirmed. Hence, the next step of the research is doing product-development to achieve product-market fit for the new products. Because of the limitation, this research only covers the concept-test in a form of a photoshop-rendered design of the products. A total of 14 people was surveyed and asked to evaluate, rate and decide three product designs for Jola’s new collection. From the survey results and analysis, only the first product achieved a threshold of 80% positive feedback while both second and third product only received 64% positive feedback. In conclusion, the first product can proceed directly to product development, undergoing sample production, product test and real production. The second and third designs will need to be re-tested before deciding if it should proceed to product development.Keywords : Fashion, Creative industry, Product-market fit, Product development, Concept-test